Towards an Islamic Human Development "A new science to be added to the contemporary jurisprudence code" - Bounquicha, Sawsen Abd-Alkarim (Journal of Islamic Sciences, 2021)
Our research shows the vast difference between the science of human development and the science of human resources and seeks to put forward a vision of an authentic Islamic human development that meets the needs of contemporary Muslims, prevents secular thought contrary to Islamic beliefs from affecting people and undermining the cultural specificity of our society, and enables Muslims to interact positively with and make use of new developments without being influenced by the negative aspects of globalization.Our research makes several proposals, including, most notably, the need to formulate a self-development model complying with Islamic sharia which is based on an authentic, developmental religious discourse reflecting the spirit of the age. The research recommends that we should defend our creed and refute every alien thought such as the meditations of the so-called energy science which are pagan rituals that have gained increasing popularity and are being promoted as a kind of therapy.
Keywords: human development; Reiki; alien thought; contemporary Muslims; Islam